Non Timber Forest Products Used for Mother and Child Health Care in Tribal and Remote Areas of Himachal Pradesh - Kumari, Anita; Sharma, Dinesh; Bawa, Rajan; Kaushal, P. (Indian Forester, 2012)
Modern healthcare system has negligible accessibility in the interior, remote and harsh areas of the northwestern Himalayas. People residing in these areas still depend upon traditional healthcare system. The study carried out in tribal and non tribal communities located in Kinnaur, Lahul, Bharmour and Pangi (tribal areas) Shilai, Churah, Parvati valley and Chhauhara (non tribal but remote areas) in Himachal Pradesh revealed that 9 species are used as tonic and as nutritional supplements by the expecting mothers. Species like Betula utilis and Dioscorea deltiodea for birth control Bunium persicum and Thymus serphyllum for relief from post delivery pain, similarly Cannabis sativa, Papaver somniferum and Selinum vaginatum are utilized as pain killers. Chenopondium album is used for the cure of chicken pox, Bombax ceiba during small pox and for urine problems, Arctium lapa and Capsella bursa pastoris are used specially in case of infants. It was also observed that due to illicit trade of the much demanded medicinal and aromatic species, many species namely Aconitum hetrophyllum, Podophyllum hexandrum, Rheum australe, etc. are on the verge of extinction. Thus there is dire need to educate the rural people to conserve their rich wealth for their own utilization.